Survey of critical biological resources, Jefferson County, Colorado, 2010-2011 - Stevens, Joe, author; Panjabi, Susan Spackman, author; Culver, Denise R., author; Smith, Pam, author; Sovell, John, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
In 2010, Jefferson County contracted with Colorado State University and the Colorado Natural Heritage Program (CNHP) to survey for critical biological resources in Jefferson County with funding provided by Jefferson County Open Space. A wetland and riparian survey was conducted concurrently with funding provided by the U.S. Environmental Protection Agency, Region 8 Wetland Program Development Grant. The purpose of this project was to provide scientific data on biological resources for land managers, planners, and the citizens of Jefferson County for conducting proactive landscape planning. This document is intended to be a tool for managing lands that support rare, imperiled and/or sensitive plants, animals, and significant plant habitats. The goal of the project was to systematically identify the locations of rare species and significant habitats. Additionally, the original paper-based National Wetland Inventory maps were digitized in accordance with the U.S. Fish and Wildlife Wetland Inventory protocol to provide an additional data resource for Jefferson County.
Prerpared for: Jefferson County Board of County Commissioners, Environmental Protection Agency, Region 8.
Keywords: wetlands; riparian areas; conservation; biodiversity